2018
DOI: 10.1515/aoas-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Humic Acids on Recovery of Salmonella Enterica Serovar Enteritidis

Abstract: Enteritidis, were carried out. In experiment 2, one-day old male broiler chickens were randomly allocate to one of two groups (n=25) with or without 0.2% of isolated HA from worm-composte, and challenged with 10 6 CFU of S. Enteritidis per chicken at 10-d old. All chicks were euthanized 24-h hours post challenge, and were for serum fluorescein isothiocyanate dextran (FITC-d) determination. A section of ileum was removed to obtain total concentration of IgA.Ceca-cecal tonsils were removed to evaluate Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The addition of humic substances to the feed did not show an increase of IgA gene expression. Similarly, Maguey-Gonzalez et al (2018) observed that humic acids in a concentration of 0.1-0.2% did not influence the total concentration of mucosal IgA in the ileum after Salmonella Enteritidis infection in neonate broiler chickens. The opposite conclusion was drawn by Wang et al (2008), who found higher relative lymphocyte counts in pigs whose feed was supplemented with 10% HS.…”
Section: Discussionmentioning
confidence: 83%
“…The addition of humic substances to the feed did not show an increase of IgA gene expression. Similarly, Maguey-Gonzalez et al (2018) observed that humic acids in a concentration of 0.1-0.2% did not influence the total concentration of mucosal IgA in the ileum after Salmonella Enteritidis infection in neonate broiler chickens. The opposite conclusion was drawn by Wang et al (2008), who found higher relative lymphocyte counts in pigs whose feed was supplemented with 10% HS.…”
Section: Discussionmentioning
confidence: 83%
“…The intestinal barrier function is closely associated with diarrhea [ 23 ]. The beneficial effects of NaH on the intestinal integrity have been found in broilers, possibly through a decreased intestinal permeability and an increased intestinal viscosity [ 24 ]. Trckova et al (2017) [ 7 ] indicated that dietary supplementation with NaH reduced the incidence and duration of diarrhea among weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Other important factors to consider are differences in the content of HA and FA, the inclusion level, and form (water or feed) and characteristics such as chain length, side-chain composition, and origin (plant, soil, peat, and coal-derived) of HS previously used in broilers [4,8,10]. It is probably that subtle differences in the composition exist between HS extracted from leonardite and lignites and those extracted from worm composts [4][5][6]. This topic also deserves further studies.…”
Section: Effect Of Dietary Treatmentsmentioning
confidence: 99%
“…Farm animals are an essential component of this triad because they are exposed to growth promoter antibiotics (GPA) to improve animal health, welfare, and productivity, and act as reservoirs and vectors of resistance genes [1,3]. For this reason, several new additives have been tested as growth promoters to reduce or alternate the inclusion of GPA in feeds, while maintaining an efficient animal production to obtain safe edible products [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation